Method for producing glass article and glass article

The heat treatment between Tg and Tc suppresses microcracks in glass manufacturing, enhancing mechanical strength and productivity by 10-70%, suitable for producing larger and more precise glass articles.

JP2025171222APending Publication Date: 2025-11-20NIPPON ELECTRIC GLASS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024076329
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-11-20

AI Technical Summary

Technical Problem

Conventional glass manufacturing processes lead to microcracks during processing, which grow under load, reducing yield and mechanical strength.

Method used

A method involving a heat treatment step at atmospheric pressure between the glass transition temperature (Tg) and crystallization temperature (Tc) of the precursor glass to suppress microcracks and enhance mechanical strength.

Benefits of technology

The method effectively suppresses microcrack formation and increases mechanical strength by 10-70% compared to precursor glass, allowing for larger and more precise glass articles with improved productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025171222000001_ABST
    Figure 2025171222000001_ABST
Patent Text Reader

Abstract

To provide a method for preventing crack generation in glass that is prone to cracking during machining, by strengthening the glass through heat treatment.SOLUTION: The method for producing a glass article of the present invention comprises: a preparation step of preparing a precursor glass; and a heat treatment step of holding the precursor glass for a certain period of time under atmospheric pressure and under temperature conditions between the glass transition temperature (Tg) of the precursor glass and the crystallization temperature (Tc) of the precursor glass, to perform heat treatment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing a glass article having improved mechanical strength, and to a glass article. [Background technology]

[0002] Conventionally, in order to obtain a glass article of a desired size, formed glass is usually subjected to processes such as cutting and grinding. For example, Patent Document 1 describes a method for grinding a plate glass in which the peripheral edge of the plate glass is brought into contact with a concave grinding surface provided on the outer periphery of a substantially disk-shaped rotating grinding wheel and ground. Furthermore, Patent Document 2 describes a method in which scribe lines are formed on a glass plate, and cutting proceeds along the scribe lines to separate the glass plate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2001-87997 [Patent Document 2] Japanese Patent Application Laid-Open No. 2006-124194 Summary of the Invention [Problem to be solved by the invention]

[0004] However, microcracks are likely to occur in glass during processing, and when a load is repeatedly applied to the formed microcracks, the cracks grow, causing breakage of the glass and reducing the yield when manufacturing glass articles.

[0005] Therefore, an object of the present invention is to provide a method for manufacturing a glass article that can suppress the occurrence of microcracks in glass and has high mechanical strength, and to provide the glass article. [Means for solving the problem]

[0006] The method for manufacturing a glass article according to aspect 1 of the present invention is characterized by comprising a preparation step of preparing a precursor glass, and a heat treatment step of holding the precursor glass at atmospheric pressure at a temperature equal to or higher than the glass transition temperature (Tg) of the precursor glass and equal to or lower than the crystallization temperature (Tc) of the precursor glass for a certain period of time.

[0007] In this way, the occurrence of microcracks in the glass can be suppressed, and the mechanical strength of the glass article can be increased.

[0008] In the method for producing a glass article according to the second aspect, in the first aspect, (Tc-Tg) is preferably 50°C or more and 350°C or less. In this way, the occurrence of microcracks in the glass article can be suppressed, the mechanical strength of the glass article can be increased, and devitrification of the glass article can be suppressed.

[0009] In the method for producing a glass article according to the third aspect, in the first or second aspect, it is preferable that Tg is 950° C. or lower.

[0010] This allows the heat treatment temperature to be lowered, thereby increasing productivity.

[0011] In the method for producing a glass article according to aspect 4, in any one of aspects 1 to 3, Tc is preferably 400° C. or higher.

[0012] In this way, devitrification of the glass article can be suppressed.

[0013] In the method for manufacturing a glass article according to aspect 5, in any one of aspects 1 to 4, it is preferable that after the heat treatment step, the crack resistance of the glass article is increased by 10% or more compared to the crack resistance of the precursor glass.

[0014] In this way, the occurrence of microcracks can be suppressed, and the mechanical strength of the glass article can be increased.

[0015] In the method for manufacturing a glass article according to aspect 6, in any one of aspects 1 to 5, it is preferable that the preparation step includes a melting step for producing molten glass and a forming step for forming the molten glass into the precursor glass.

[0016] In this way, glass articles of various shapes and sizes can be easily manufactured.

[0017] A glass article according to a seventh aspect of the present invention is characterized in that, when the arithmetic mean height of the surface before the hydrofluoric acid etching treatment is (Sa1) and the arithmetic mean height of the surface after the hydrofluoric acid etching treatment is (Sa2), (Sa2-Sa1) is 0.1 nm or more and 40 nm or less.

[0018] In this way, the occurrence of microcracks can be suppressed, and the mechanical strength of the glass article can be increased.

[0019] In the glass article according to the eighth aspect, in the seventh aspect, it is preferable that the glass article be amorphous.

[0020] This makes it easier to obtain glass articles with high surface accuracy.

[0021] In the glass article according to aspect 9, in aspect 7 or aspect 8, the maximum length of the glass is preferably 50 mm or more and 20,000 mm or less.

[0022] In this way, a large glass article can be produced, and the glass article can be cut into a large number of glass articles, thereby improving manufacturing efficiency.

[0023] The glass article according to the tenth aspect is preferably used for a window in any one of the seventh to ninth aspects. [Effects of the Invention]

[0024] According to the present invention, it is possible to provide a method for manufacturing a glass article that can suppress the occurrence of microcracks in glass and has high mechanical strength, and a glass article. [Brief explanation of the drawings]

[0025] [Figure 1] 1 is a flowchart of a method for manufacturing a glass article according to the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0026] Hereinafter, an example of a preferred embodiment for carrying out the present invention will be described. However, the following embodiment is merely an example, and the present invention is not limited to the following embodiment in any way.

[0027] In this embodiment, a method for manufacturing a glass article will be described. Fig. 1 is a flowchart showing the method for manufacturing a glass article in this embodiment. As shown in Fig. 1, this embodiment includes a preparation step S1 for preparing a precursor glass, and a heat treatment step S2 for holding the precursor glass for a certain period of time under atmospheric pressure and at a temperature between the glass transition temperature (Tg) of the precursor glass and the crystallization temperature (Tc) of the precursor glass, thereby performing heat treatment.

[0028] In the precursor glass preparation step S1, the precursor glass is prepared by carrying out a melting step S11 for producing molten glass and a shaping step S12 for shaping the molten glass. In this way, the precursor glass can be obtained by melting the glass in a container made of refractory material or platinum and then pouring it out, so that the precursor glass can be produced relatively easily.

[0029] In the melting step S11, a raw material batch having a predetermined composition is charged into a melting crucible or a glass melting furnace, and the raw material batch is melted at 800 to 1700° C. to obtain molten glass.

[0030] The melting method is preferably a method using any one of flame melting using a burner or the like, electric melting by electrical heating, melting by laser irradiation, and melting by plasma, or a combination of two or more of these methods.

[0031] In the forming step S12, the molten glass obtained in the melting step S11 is poured from the melting crucible or glass melting furnace and formed into a predetermined shape to obtain a precursor glass. In the forming step S12, methods such as the overflow method, float method, down-draw method, slot-down method, blow method, press method, roll method, bushing method, and tube drawing method can be used.

[0032] Precursor glasses include Li2O-Al2O3-SiO2-based crystalline glass, MgO-Al2O3-SiO2-based crystalline glass, B2O3-SiO2-based crystalline glass, Al2O3-B2O3-SiO2-based crystalline glass, R2O-SiO2-based crystalline glass (R: alkali metal element), R'O-SiO2-based crystalline glass (R': alkaline earth metal element), F-SiO2-based crystalline glass, P2O5-based crystalline glass, P2O5-SiO2-based crystalline glass, and Fe2O3-SiO2-based crystalline glass.

[0033] When the precursor glass is Li2O-Al2O3-SiO2-based crystallizable glass, the composition is preferably SiO2 55-75%, Al2O3 15.5-27%, Li2O 2-25.6%, TiO2 1.5-3%, TiO2 + ZrO2 3.8-5%, and SnO2 0.1-0.5%.

[0034] The glass transition temperature (Tg) of the precursor glass is preferably 400°C or higher, more preferably 450°C or higher, particularly preferably 500°C or higher, and preferably 950°C or lower, more preferably 900°C or lower, particularly preferably 850°C or lower. When Tg is equal to or higher than the lower limit, the heat resistance of the glass can be improved. When Tg is equal to or lower than the upper limit, the melting temperature can be lowered when producing the precursor glass, making it easier to prepare the precursor glass.

[0035] The crystallization temperature (Tc) of the precursor glass is preferably 400°C or higher, more preferably 450°C or higher, most preferably 500°C or higher, and preferably 1050°C or lower, more preferably 1000°C or lower, and most preferably 950°C or lower. If Tc is above the lower limit, precipitation of crystals in the glass article can be suppressed in the subsequent heat treatment step S2. If Tc is below the upper limit, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be more easily obtained.

[0036] Tg and Tc can be measured by differential scanning calorimetry (DSC) or differential thermal analysis (DTA).

[0037] In the heat treatment step S2, the precursor glass obtained in the molding step S12 is subjected to a heat treatment at atmospheric pressure at a temperature equal to or higher than the glass transition temperature (Tg) of the precursor glass and equal to or lower than the crystallization temperature (Tc) of the precursor glass for a certain period of time. Note that, before the heat treatment step S2, another step, such as a processing step of machining the precursor glass, may be included.

[0038] The atmospheric pressure here is 7.0 x 10 4 Pa~1.3×10 5 This refers to the range of Pa.

[0039] The heat treatment temperature in the heat treatment step S2 is Tg or higher and Tc or lower, preferably Tg+10°C or higher, more preferably Tg+20°C or higher, particularly preferably Tg+30°C or higher, preferably Tc-80°C or lower, more preferably Tc-90°C or lower, and particularly preferably Tc-100°C or lower. When the heat treatment temperature is above the lower limit, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be easily obtained. When the heat treatment temperature is below the upper limit, crystal precipitation in the resulting glass article can be suppressed.

[0040] The heat treatment time of the heat treatment step S2 is preferably 1 hour or more, more preferably 3 hours or more, preferably 100 hours or less, more preferably 75 hours or less. When the heat treatment time is equal to or greater than the lower limit, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be easily obtained. When the heat treatment time is equal to or less than the upper limit, deformation and crystal precipitation of the resulting glass article can be suppressed.

[0041] (Tc-Tg) is preferably 50°C or higher, more preferably 100°C or higher, particularly preferably 150°C or higher, preferably 350°C or lower, more preferably 300°C or lower, and most preferably 250°C or lower. When (Tc-Tg) is equal to or higher than the lower limit, deformation and crystal precipitation of the resulting glass article can be suppressed. When (Tc-Tg) is equal to or lower than the upper limit, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be more easily obtained.

[0042] After the heat treatment step S2, the crack resistance of the glass article is preferably increased by 10% or more, more preferably by 30% or more, even more preferably by 50% or more, and most preferably by 70% or more, compared to the crack resistance of the precursor glass. In this way, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be more easily achieved.

[0043] Crack resistance was measured using the following procedure. First, glass was processed into a 25mm x 30mm plate, and both sides were parallel and mirror-polished to a thickness of 4mm. This was placed on a test stage with the sample surface horizontal in an air atmosphere at 25°C and 30% relative humidity. A Vickers indenter was then driven into the sample surface at an arbitrary load, and the number of cracks that appeared from the four vertices of the indentation was counted within 15 seconds after the indentation was completed (maximum of four per indentation). This process was repeated 20 times for each load, and the load at which the probability of crack occurrence was 50% (40 / 80 cracks) was measured as the crack resistance. Measurements were performed using a Matsuzawa Seiki MTX-50 microhardness tester.

[0044] The density of the glass article after heat treatment step S2 is preferably increased by 0.01% or more, more preferably by 0.1% or more, and most preferably by 0.4% or more, compared to the density of the precursor glass before heat treatment step S2. In this way, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be more easily achieved.

[0045] The glass article of the present invention has an arithmetic mean height (Sa1) of the surface before the hydrofluoric acid etching treatment, When the arithmetic mean height of the surface after hydrofluoric acid etching is (Sa2), (Sa2-Sa1) is preferably 0.1 nm or more and 40 nm or less. The lower limit is preferably 0.5 nm or more, 1 nm or more, 2 nm or more, 3 nm or more, 4 nm or more, and particularly 5 nm or more. The upper limit is preferably 30 nm or less, 25 nm or less, 20 nm or less, and particularly 15 nm or less. When (Sa2-Sa1) is equal to or greater than the lower limit, the occurrence of microcracks in the glass of the present invention can be suppressed, and the effect of increasing the mechanical strength of the glass article can be more easily achieved. When (Sa2-Sa1) is equal to or less than the upper limit, crystal precipitation in the glass article is suppressed.

[0046] The hydrofluoric acid etching treatment was carried out as follows: First, the glass was processed into a plate measuring 25 mm x 30 mm and 2 mm thick, and subjected to the heat treatment step S2. The surface of the glass was scribed with a diamond cutter and broken in half lengthwise. The broken surface was immersed in a 46% hydrofluoric acid solution for 2 minutes, and then etched.

[0047] The arithmetic mean height of the uneven surface after etching of the folded surface was evaluated using a Keyence VK-250 / 260 shape analysis laser microscope and a VK-H1XV2 / H1XM multi-file analysis application. A 150x lens (Nikon APOx150 objective lens) was used to capture images with a high-resolution (2048 x 1536) measurement size. A Gaussian filter, S-filter: 0.25 μm, F-operation (shape correction): waviness removal (strength 5), and L-filter: 0.1 mm were used to calculate the arithmetic mean height (Sa) for an arbitrary area of ​​50 μm x 50 μm of the captured image.

[0048] The glass article of the present invention is preferably amorphous. This makes it easier to obtain a glass article with high surface precision. Whether a glass article is amorphous can be determined by whether or not crystalline diffraction lines are detected and only amorphous halos appear in a diffraction line profile at 2θ values ​​of 10 to 60° obtained by powder X-ray diffraction measurement using CuKα radiation.

[0049] The glass article of the present invention preferably has a maximum length of 50 mm or more, more preferably 500 mm or more, and preferably 20,000 mm or less, more preferably 10,000 mm or less. This allows the glass article to be manufactured in a large size and can be cut into a large number of glass articles, thereby improving production efficiency.

[0050] The glass article of the present invention is preferably used for windows, and because it has high crack resistance, it can be suitably used for glass windows. [Example]

[0051] The present invention will be described in detail below based on examples. Note that the following examples are merely illustrative and are not intended to limit the scope of the present invention.

[0052] Table 1 shows examples of the present invention (samples Nos. 1 to 4) and a comparative example (sample No. 5).

[0053] [Table 1] Each sample was prepared as follows. Glass raw materials were blended to obtain a Li2O-Al2O3-SiO2-based crystalline aluminosilicate glass having the following composition (mass%): SiO2 66.3%, Al2O3 22%, Li2O 4%, TiO2 2%, ZrO2 2%, BaO 1.5%, Na2O 0.5%, K2O 0.5%, PO 51%, and SnO 0.2%. The blended raw material batch was then placed in a melting furnace and melted at 1650°C for 20 hours. The mixture was then refined and stirred to obtain a homogeneous molten glass. The resulting molten glass was poured from the melting furnace and formed into a flat plate to obtain a glass precursor. The resulting precursor glass was heat-treated under the conditions listed in Table 1 to obtain a glass article. Sample No. 5 was not heat-treated, and the precursor glass itself was used as the glass article. For each sample obtained, the density, Young's modulus, crack resistance CR, Vickers hardness Hv, and fracture toughness K C The Tg and Tc of the precursor glass were also measured and found to be 710°C and 890°C, respectively.

[0054] The density is a value measured by Archimedes' method.

[0055] The Young's modulus is a value measured by a resonance method.

[0056] The Vickers hardness Hv is a value measured by pressing a Vickers indenter with a load of 100 gf using a Vickers hardness tester.

[0057] Fracture toughness K Cis a value measured using the indentation-fracture method (IF method) as defined in the Japanese Industrial Standard JISR1607 "Room temperature fracture toughness test method for fine ceramics."

[0058] For Samples Nos. 1 to 4, which are examples, the change in arithmetic mean surface height (Sa2-Sa1) before and after hydrofluoric acid etching increased by 1 to 3 nm, while for Sample No. 5, which is a comparative example, there was no change in the change in arithmetic mean surface height (Sa2-Sa1) before and after hydrofluoric acid etching.

[0059] Furthermore, the crack resistance of Samples Nos. 1 to 4, which are examples, increased by 35 to 75% due to the heat treatment. On the other hand, Sample No. 5, which is a comparative example, was not subjected to heat treatment, and therefore had a lower crack resistance than the examples. [Explanation of symbols]

[0060] S1: Preparation process S2: Heat treatment process S11: Melting process S12: Molding process

Claims

1. a preparation step of preparing a precursor glass; a heat treatment step of holding the precursor glass at a temperature equal to or higher than the glass transition temperature (Tg) of the precursor glass and equal to or lower than the crystallization temperature (Tc) of the precursor glass for a certain period of time under atmospheric pressure; A method for manufacturing a glass article, comprising:

2. 2. The method for producing a glass article according to claim 1, wherein (Tc - Tg) is 50°C or more and 350°C or less.

3. 3. The method for producing a glass article according to claim 1, wherein Tg is 950° C. or less.

4. 3. The method for producing a glass article according to claim 1, wherein Tc is 400° C. or higher.

5. 3. The method for manufacturing a glass article according to claim 1, wherein after the heat treatment step, the crack resistance of the glass article is increased by 10% or more compared to the crack resistance of the precursor glass.

6. 3. The method for manufacturing a glass article according to claim 1, wherein the preparation step comprises a melting step for producing molten glass and a forming step for forming the molten glass into the precursor glass.

7. The arithmetic mean height of the surface before the hydrofluoric acid etching treatment is (Sa1), When the arithmetic mean height of the surface after the hydrofluoric acid etching treatment is (Sa2), A glass article characterized in that (Sa2-Sa1) is 0.1 nm or more and 40 nm or less.

8. 8. The glass article according to claim 7, which is amorphous.

9. 9. The glass article according to claim 7, wherein the maximum length is 50 mm or more and 20,000 mm or less.

10. 9. A glass article according to claim 7 or 8, which is used for a window.

Citation Information

Patent Citations

  • JP87997A

  • JP124194A